COVID-19 pre-pandemic tourism forecasts and post-pandemic signs of recovery assessment for Portugal - Maria de Fátima Brilhante; Maria Luísa Silva Rocha (Research in Globalization, 2023)
Over the last decades the tourism sector has played an increasingly important role in the socio-economic development of Portugal. We analyze data from the last fifty years from Portugal, comparing non-pandemic forecasts derived with ARIMA time series models for the triennium 2020-2022, that is, forecasts obtained under the assumption that the COVID-19 pandemic would not have happened, to actual pandemic values as means to assess the impact of the pandemic on the annual numbers of guests and overnight stays in that period. The results show that full recovery has been reached in Portugal for the number of overnight stays in 2022, and individually in each main region of the country (mainland Portugal, Madeira and the Azores). However, the same cannot be said of the recovery of the number of guests, except for Madeira in 2022, whose recorded value exceeded the corresponding non-pandemic forecast value.
Keywords: 330; Guests; Overnight stays; Portugal; Pre-pandemic forecasts; Recovery; Tourism